Executive Functions in Psychiatric Disorders - Rodrigo Grassi-Oliveira (Frontiers Research Topics, 2017)
Executive Functions comprise a range of neuropsychological processes related to intentional behavior and cognitive control. There are several theoretical models defining and explaining the concept of Executive Functions. Most of these models consider that the term Executive Functions encompasses cognitive process as working memory, cognitive flexibility, inhibitory control and other complex functions as planning, problem-solving and abstract reasoning. Other models argue that motivational and emotional functions, such as affective decision-making, reside under the concept of Executive Function. Much evidence supports how complex cognitive functions are related to the physiological activity of brain networks, including the frontal cortex and its connections with subcortical structures. Several psychiatric disorders related to impairment in these brain networks (eg., bipolar disorder, schizophrenia, ADHD, obsessive-compulsive disorder, and drug addiction) leading to deficits in Executive Functions. These cognitive deficits affect patients' everyday functioning, worsening the clinical course of the disease. For example, deficits in Executive Functions are related to suicide behavior in bipolar disorder patients. Furthermore, these deficits also relate to obesity, a lack of adherence to treatment and an underperformance in the workplace and educational settings. The understanding of the role of deficits in Executive Functions, including its neurobiological basis, developmental trajectories, and relationship with clinical outcomes, is fundamental to improve clinical management of psychiatric patients. This research topic includes 13 articles with interdisciplinary contributions related to the understanding of the deficits in Executive Functions and its relationship with clinical manifestations in psychiatric disorders.